The Relationship Between Environmentally Friendly Product Innovation, Sustainable Marketing Strategy, and Customer Satisfaction to Financial Performance in the Sustainable Fashion Industry in Indonesia - Anita, Siska Yuli; Mu'min, Halek; Megawati, Eka; Setiawati, Rahmi; Utomo, Bekti (West Science Interdisciplinary Studies, 2024)
This research investigates the interplay between eco-friendly product innovation, sustainable marketing strategy, customer satisfaction, and financial performance in the sustainable fashion industry of Indonesia. A quantitative approach using structural equation modeling (SEM) with partial least squares (PLS) analysis was employed to analyze data collected from consumers and key stakeholders in the Indonesian fashion market. The findings reveal significant positive relationships between eco-friendly product innovation, sustainable marketing strategy, customer satisfaction, and financial performance. Specifically, eco-friendly product innovation and sustainable marketing strategy were found to positively influence customer satisfaction and financial performance, highlighting the importance of integrating sustainability principles into product development and marketing strategies. Additionally, customer satisfaction emerged as a critical driver of financial performance, underscoring the importance of delivering value and positive experiences to consumers in the sustainable fashion sector. These findings have important implications for fashion businesses, policymakers, and other stakeholders seeking to promote sustainability and economic growth in the Indonesian fashion industry.